ANALISA PENGARUH VARIASI PUTARAN SPINDEL DAN VARIASI GERAKAN MAKAN TERHADAP KEKASARAN PERMUKAAN PEMBUBUTAN DALAM MATERIAL ST50 - ; Hartono, Priyagung; Margianto, Margianto (UNIVERSITAS ISLAM MALANG, 2015)
Lathe machining process is a process to produce engine parts or cylindrical part done by using lathe machine. The basic principles can be defined as the process of machining outer surface of cylindrical objects or flat lathe process and also the inner surface finish by the lathe process. Lathe itself is a process that feeds the workpiece cutting done by rotating the workpiece and then imposed on the chisel driven translational parallel to the spin axis of the workpiece. CNC lathe machines are widely used by manufacturing industries, training centers and schools such as NC machine CNC lathe is a machine that is capable of receiving the data by command, processing and output it in the form of movements on cutting tools. Spindle rotational speed, depth of cut, feeding and also includes geometry cutting tools affect the roughness of the workpiece. In this reseach would be seen whether there is influence spindle rotational speed, depth of cut, feeding and also includes geometry cutting tools at the EMCO CNC Turning Machines 242 against the workpiece of surface roughness. The research method used was experimental and statistical methods. The research was conducted at the Laboratory of Department of Mechanical Engineering, State Polytechnic of Malang. In this research used steel grade ST50 and type of cutting tools material grade is HSS, where the observation was performed 5 times and the variation of the cutting speed as much as 4 variations. Data collected by using the method of observation and documentation. The data obtained were then tested with SPSS 17 for Windows and Microsof Excel 2007. There are changes in surface roughness of the workpiece spindle rotational speed, depth of cut, feeding. The higher the rotation spindle, more smooth surface of the workpiece, and the deeper the depth of cut so more rough the surface of the workpiece. Judging from SPSS software test on the effect of cutting speed variation of the surface roughness of the workpiece obtained F table larger than F count and F Anova F1 count : 0,869 < Ftabel :3,86 and F2 hitung : 2,769 < Ftabel :3,86 with level of significant ? : 5%.